“Experience Journey”Mendesain Rangkaian Aktivitas Perjalanan Wisata Budaya - Sudhiastiningsih, Ni Nyoman Sri Natih (Journal of Indonesian Tourism and Policy Studies, 2016)
This manuscript describes the phenomenon of design collaboration model, multivillage approach for developing cultural tourism in Ngada Regency, East Nusa Tenggara. This paper aims to describe the existence of design as a tool for creating changes impacting sustainable livelihoods and develop products to strengthen the cultural tourism in the context of historical, social and cultural. “Experience Journey” as a reinforcement for the excavation of local values dedicated to the development of cultural tourism. Using an ethnographic approach and design thinking, the author can describe a series of memorable and meaningful activities as a touch of design and various product of collaboration that support the creation of values typical Ngada specific experience. During the implementation of IKKON’s program, indigenous communities in three traditional villages provide various responses ranging from designing “Experience Journey,” product prototyping a